Identification of metabolites produced by Phanerochaete chrysosporium in the presence of amlodipine orotate using metabolomics - De Sotto, R. B.; Kim, K. I.; Kim, S.; Song, K. G.; Park, Y. (IWA PUBLISHING, 2015)
Pharmaceuticals are very useful in treating human diseases but they are excreted to the environment sometimes in their original form or as byproducts of human metabolism. Pharmaceuticals and their metabolites have been proven by studies to be harmful to non-target ecological species and may be persistent in different water matrices. In this regard, there is an emergent need to eliminate these compounds to prevent their adverse effects on aquatic species. Biodegradation using white-rot fungi is a promising technology for the removal of recalcitrant compounds; however, products of fungal biodegradation can also be detrimental. In this novel study, we evaluated the ability of Phanerochaete chrysosporium to degrade amlodipine, an anti-hypertensive drug which was recently found in water systems. Analysis of amlodipine metabolites was done using quadrupole time-of-flight liquid chromatography mass spectrometry after the degradation set-up of 120 hours. Pharmaceutical degradation was seen using triple quadrupole liquid chromatography tandem mass spectrometry. Ninety-two significant metabolites (P-value <= 0.05) were significantly expressed after false discovery rate adjustment at a significance threshold of q = 0.05. Pyridine derivatives which were identified from samples became the basis of the proposed degradation pathway of amlodipine in this study.
Keywords: WASTE-WATER EFFLUENTS; HUMAN PHARMACEUTICALS; ENVIRONMENT; REMOVAL; FATE